Draft genome sequence data of vibrio harveyi VH1 isolated from a diseased tiger grouper, epinephelus fuscoguttatus , cultured in Malaysia - Amatul-Samahah, Md. Ali; Mohamad, Aslah; Al-saari, Nurhidayu; Saad, Mohd Zamri; Azmai, Mohamad Noor Amal; Yusof, Mohd Termizi; Ina-Salwany, Md. Yasin; Tanaka, Mami; Mino, Sayaka; Sawabe, Tomoo (Elsevier, 2022)
Vibriosis accounts for 66.7% of diseases reported in groupers’ cultures and affects almost all stages of growth. The dis- ease could lead up to mortality up to 50% mortality, and it was reported that high stocking density and poor fish han- dling were among the factors that contributed to the dis- ease dissemination. V. harveyi has been reported to be among the causative agent and has caused acute mortality in cage groupers. In this study, we report the genome of V. har- veyi VH1 isolated from a diseased tiger grouper Epinephelus fuscoguttatus , reared in a cage farm located in the coastal area of Langkawi.